Use of short-term steroids in the prophylaxis of atrial fibrillation after cardiac surgery - Zeyad Al-Shawabkeh (Journal of the Saudi Heart Association, 2017)
Objectives: To assess the effectiveness of corticosteroids in the prophylaxis of postoperative atrial fibrillation (AF) in patients undergoing elective coronary artery bypass grafting or valvular heart surgery in terms of reducing its incidence and decreasing the length of hospital stay. Methods: This prospective double blinded randomized study was conducted at Queen Alia Heart Institute (Amman, Jordan) from June 2014 to June 2015 on 340 patients who underwent their first on-pump elective coronary artery bypass grafting (CABG) alone or combined with valvular surgery. Inclusion criteria consisted of elective first time CABG or combined with valvular surgery, use of β-adrenergic blockade, and normal sinus rhythm. Exclusion criteria included a history of heart block, previous episodes of AF or flutter, uncontrolled diabetes mellitus, history of peptic ulcer disease, systemic bacterial or mycotic infection, permanent pacemaker, and any documented or suspected supraventricular or ventricular arrhythmias. Patients were randomized into two equal groups (n = 170 each), then each group was subdivided into patients who underwent CABG alone (n = 120), and patients underwent valvular heart surgery with or without CABG (n = 50). In the treatment group, patients were given 1 g of methylprednisolone before cardiopulmonary bypass then 100 mg of hydrocortisone every 8 hours for the first 3 days postoperatively. The primary endpoint was the overall occurrence of postoperative AF. Results: AF developed in 21.1% (36 patients) in the treatment group in contrast to 38.2% (65 patients) in the control group (p < 0.05). In the subdivided groups (CABG only), approximately 20% (24 patients) developed AF in the treatment group in contrast to 35% (42 patients) in the control group (p < 0.05). In the other group, (CABG + VALVE) 24% (12 patients) developed AF compared with 46% (23 patients) in the control group (p < 0.05). The length of hospital stay was 6.02 ± 11.23 days in the treatment group while it was 5.98 ± 1.86 days in the control group, which was found to be statistically nonsignificant. No statistical significant difference in the rate of postoperative complications including mediastinitis as well superficial wound infections was observed between the two groups. Conclusion: Prophylactic short-term use of steroids both intraoperatively and postoperatively proved to be safe and effective in reducing the incidence of postoperative AF in patients undergoing CABG alone or combined with valve surgery.